The storytime handbook a full year of themed programs, with crafts and snacks - Miller, Nina Schatzkamer (McFarland & Company, Inc., Publishers, 2014)
Fresh, fun ideas for children's storytime fill this book. The author, a long-time storytime facilitator, has put together 52 weekly themes plus additional plans for holidays, all with detailed instructions for talking about the theme and choosing the books, crafts, songs, poems, games and snacks. Each storytime idea is illustrated with photographs of a suggested craft and snack for easy reference. Libraries, bookstores, preschools and parents alike can use this book to offer themed storytimes that include discussion, literature, art, music, movement and food. Options are provided for each storytime, so the ideas can be used year after year.--Provided by publisher.